Transparent microwave crossover for transparent Butler matrix using micro-metal mesh conductive film - Sa'Ad, B. M. (2015)
This paper presents the design of a novel transparent microwave crossover (MC) for a transparent Butler matrix (BM) using a proprietary self-assembling nano-particle technology based Micro-metal Mesh (MM) conductive film. The transparent MM conductive film has a sheet resistance of 0.7 ohms/sq and a visible-light transmission of 75 %, resulting in high transparency and good conductivity, respectively. The proposed transparent crossover is placed on a 2 mm-thick glass substrate of dielectric 5.7 and designed to operate at 2.45 GHz. A layer of MM film placed at the back of the glass serves as a ground. The transparent MC delivered a measured crossing coupling of 1.5 dB. The transparent MC can be used as a building block for realizing a transparent Butler Matrix (BM) Beam Forming Network (BFN) for inter/intra-vehicle wireless communication (IIVWC) in Intelligent Transport System (ITS). Besides being transparent, the proposed MC has a 0.25 mm profile excluding the glass substrate. These advantages greatly enhance the MC's potential to be used also as a BM building component that can be mounted onto the glass surfaces of buildings for future 5G indoor wireless communications.